2017
DOI: 10.1038/s41598-017-01909-8
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of caloric restriction on post-incisional pain in nonobese rats

Abstract: Caloric restriction (CR) increases lifespan, retards physiological signs of aging, and delays a variety of diseases. Reduction of inflammatory response was proposed as one of the molecular mechanisms for how CR exerts beneficial effects. The present study investigated the effects of CR on postoperative pain in rats. Adult nonobese rats were divided into two dietary groups, an ad libitum fed group (AL) and a caloric restriction group (CR) that was provided with 60% of the food intake of AL rats. After 6 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In another rat study using the paw incision model, caloric restriction further reduced the magnitude of mechanical hypersensitivity compared to normal low-fat chow feeding (Liu et al, 2017), complementing the findings of the high-fat diet studies.…”
mentioning
confidence: 64%
“…In another rat study using the paw incision model, caloric restriction further reduced the magnitude of mechanical hypersensitivity compared to normal low-fat chow feeding (Liu et al, 2017), complementing the findings of the high-fat diet studies.…”
mentioning
confidence: 64%
“…Additionally, with LitLab™, we found strong associations between the genes that comprised our organ network and pain signaling and physiological response to pain. In line with this, fasting and calorie restriction have an analgesic effect in murine models [ [77] , [78] , [79] ], and intermittent fasting was proposed as a non-invasive, inexpensive, and implementable strategy to chronic pain treatment (reviewed in [ 80 ]). Key underlying mechanisms in fasting-enhanced neuroplasticity include a short-term corticosterone increase, a reduction in GABAergic inhibition, and an increase in protein chaperons and neurotrophic growth factors such as brain-derived neurotrophic factor (BDNF), which exerts positive effects on neuronal survival and synaptogenesis [ [81] , [82] , [83] ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few reports regarding pathological pain hypersensitivity relevant to oral mucosal injury, although previous studies have shown that post-traumatic pain hypersensitivity was induced in a traumatic injury model (Kumar, Sarumathi, Veerabahu, & Raman, 2013;Liu et al, 2017;Mamet et al, 2017). Clinically, it has long been known that the oral mucosa is unique in its mechanical and thermal sensitivity compared with that of the skin, suggesting that the mechanical and thermal sensory mechanisms in the oral mucosa are different from those of the body's surface (Green & Gelhard, 1987;Komiyama & De Laat, 2005).…”
Section: Discussionmentioning
confidence: 99%